Motivations for birdwatching scale – Developing and testing an integrated measure on birding motivations - Randler, Christoph; Großmann, Nadine (Frontiers in Bird Science, 2022)
Birding has become a widespread, nature-related outdoor leisure activity. However, birding motivation has received little attention in research on this leisure activity so far. Since previous work showed some inconsistencies that are based on different measurements and concepts, the current study aimed at unifying and broadening the construct of birding motivation. For this purpose, we summarized the previous attempts to assess and categorize birding motivation and tried to unify them in one measurement model. Starting point was a widely accepted model on outdoor recreation to which further dimensions have been added. We investigated birders (N=569) from German speaking countries regarding their birding motivations, birding specialization, and participation in various bird-related projects. Exploratory factor analysis revealed six motivation factors: Enjoyment had the highest scale mean, followed by achievement, conservation, detachment, social, and finally reputation. Confirmatory factor analysis showed a better fit of the posited six-factor model compared to the previous three-factor model supporting the initial concept of adding further scales to cover the motivational constructs more widely. Higher skilled, specialized and involved birders showed higher motivation in the dimensions conservation, social, and reputation. Conservation motivation was highly correlated with submitting observations to a citizen sciences portal and with participating in breeding bird surveys or waterbird counts. With our results, we provide evidence forexpand the basic three-dimensional model of recreation motivation as well as forwith the additional dimensions expanded model with the additional dimensions conservation, detachment, and reputation.